Analisis Efisiensi Industri Dana Pensiun: Penggunaan Metode Non Parametrik Data Envelopment Analyst (DEA) - , Stefanus Sarikusumo, Dr. Khomsiyah. M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Efficiency is one of the performance parameters which theoretically is one performance that underlies the entire performance of an organization. The ability to produce maximum output with the existing input is a measure of expected performance. At the time of measurement of efficiency is, companies are faced on how to obtain the optimal level of output with existing levels of inputs, or get the minimum input level to the level of output. Research to calculate the efficiency of the Pension Fund Industry is required as a benchmark in the industry to be more competitive. This study also provides an opportunity to the public about the performance efficiency of the Pension Fund Industry Pension Fund in addition to introducing its own function. Measurement of efficiency can be divided in parametric (Stochastic Frontier Approach) and nonparametric (Data Envelopment Analysis). Use of Data Envelopment Analysis (DEA) to measure the efficiency of each Decision Making Units (DMUs), which is obtained as the maximum of the weight ratio of outputs to weighted inputs. DEA is a relative efficiency measure, which measures the inefficiency of DMUs with others who are considered the most efficient in the existing data sets. The variables in this research using two variable inputs and two outputs variables. Input variables consist of a sales charge and the initial investment while the variable outputs consist of the total investment income and total operating performance. Testing the efficiency of this data using the Pension Funds Financial Institutions in Indonesia. Data - average players in the industry of Financial Institutions Pension Fund is 23 companies. The research data were taken for five years from 2005 until 2009 from several accounts in the financial statements of the Pension Fund. During the five-year study of 22 Pension Funds Financial Institutions Pension Fund are annually obtained always have value - average 100% of Pension Fund of Central Java Regional Development Bank. Research results - average five-year highest efficiency was also obtained from Sinarmas Pension Fund, Aviva, Avrist and AIA.